Optogenetic stimulation of the brainstem dorsal motor nucleus ameliorates acute pancreatitis - Thompson, Dane A.; Tsaava, Tea; Rishi, Arvind; Nadella, Sandeep; Mishra, Lopa; Tuveson, David A.; Pavlov, Valentin A.; Brines, Michael; Tracey, Kevin J.; Chavan, Sangeeta S. (Frontiers in Immunology, 2023)
Introduction Inflammation is an inherently self-amplifying process, resulting in progressive tissue damage when unresolved. A brake on this positive feedback system is provided by the nervous system which has evolved to detect inflammatory signals and respond by activating anti-inflammatory processes, including the cholinergic anti-inflammatory pathway mediated by the vagus nerve. Acute pancreatitis, a common and serious condition without effective therapy, develops when acinar cell injury activates intrapancreatic inflammation. Prior study has shown that electrical stimulation of the carotid sheath, which contains the vagus nerve, boosts the endogenous anti-inflammatory response and ameliorates acute pancreatitis, but it remains unknown whether these anti-inflammatory signals originate in the brain. Methods Here, we used optogenetics to selectively activate efferent vagus nerve fibers originating in the brainstem dorsal motor nucleus of the vagus (DMN) and evaluated the effects on caerulein-induced pancreatitis. Results Stimulation of the cholinergic neurons in the DMN significantly attenuates the severity of pancreatitis as indicated by reduced serum amylase, pancreatic cytokines, tissue damage, and edema. Either vagotomy or silencing cholinergic nicotinic receptor signaling by pre-administration of the antagonist mecamylamine abolishes the beneficial effects. Discussion These results provide the first evidence that efferent vagus cholinergic neurons residing in the brainstem DMN can inhibit pancreatic inflammation and implicate the cholinergic anti-inflammatory pathway as a potential therapeutic target for acute pancreatitis.